Introduction of Gluten, HLA Status, and the Risk of Celiac Disease in Children - Lionetti, Elena; Castellaneta, Stefania; Francavilla, Ruggiero; Pulvirenti, Alfredo; Tonutti, Elio; Amarri, Sergio; Barbato, Maria; Barbera, Cristiana; Barera, Graziano; Bellantoni, Antonella; Castellano, Emanuela; Guariso, Graziella; et al. (The New England journal of medicine, 2014)
A total of 832 newborns with a familial risk of celiac disease underwent genotyping and were assigned to introduction of dietary gluten at 6 or 12 months of age. There was no between-group difference in the prevalence of the disease at 5 years of age. Celiac disease is a systemic immune-mediated disorder caused by the ingestion of gluten-containing grains (wheat, rye, and barley) in genetically susceptible persons. It is one of the most common lifelong disorders, affecting approximately 1% of the population in Europe and North America 1 , 2 ; the prevalence of this disease is higher among persons who have first-degree relatives with celiac disease (10 to 15%). 3 , 4 The prevalence of celiac disease has increased in developed countries over recent decades; this finding points to the role of one or more possible environmental triggers other than gluten. 5 Genetic background plays a key role in . . .